2015
DOI: 10.15809/irriga.2015v1n1p248
|View full text |Cite
|
Sign up to set email alerts
|

Épocas De Poda Para a Amoreira-Preta Cultivada Em Região Subtropical

Abstract: ÉPOCAS DE PODA PARA A AMOREIRA-PRETA CULTIVADA EM REGIÃO SUBTROPICAL  SARITA LEONEL1 E DANIELA MOTA SEGANTINI2 1 Eng. Agrônomo, Doutor, Departamento de Horticultura, Universidade Estadual Paulista "Júlio de Mesquita Filho", Botucatu-SP, CEP 18.610-307, e-mail: sarinel@fca.unesp.br2 Eng. Agrônomo, Doutoranda do PPGA/Horticultura, Departamento de Horticultura, Universidade Estadual Paulista "Júlio de Mesquita Filho", Botucatu-SP, CEP 18.610-307, e-mail: dani_segantini@hotmail.com  1 RESUMO As frutas ofertadas fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
1
1
Order By: Relevance
“…However, our results were below those found by Leonel and Segantini (2015), who evaluated blackberry in a subtropical region and found masses of 7.51 g and 7.12 g for pruning carried out in July and August, respectively. Ferreira et al (2016) observed an average weight of 5.1 and 5.4 g fruit of the cv.…”
Section: Resultscontrasting
confidence: 99%
“…However, our results were below those found by Leonel and Segantini (2015), who evaluated blackberry in a subtropical region and found masses of 7.51 g and 7.12 g for pruning carried out in July and August, respectively. Ferreira et al (2016) observed an average weight of 5.1 and 5.4 g fruit of the cv.…”
Section: Resultscontrasting
confidence: 99%
“…Resultados semelhantes foram encontrados em São Manuel-SP onde as diferentes épocas de poda tiveram efeito significativo e seu atraso resultou em menor número de frutos por planta. SEGANTINI, 2015;SEGANTINI et al, 2014). Em Marechal Cândido Rondon-PR, foi observada diferença significativa entre as seis diferentes épocas de poda trabalhadas, nas safras 2008/09 e 2009/10, onde as plantas podadas entre o início de julho e início de agosto foram aquelas que apresentaram maior número de frutos, decrescendo à medida que a poda foi antecipada ou adiada.…”
Section: Resultsunclassified